Preliminary population studies of the grassland swallowtail butterfly Euryades corethrus (Lepidoptera, Papilionidae) - Atencio, Guilherme (2023)
Euryades corethrus is a Troidini butterfly (Papilionidae, Papilioninae), endemic to grasslands in southern Brazil, Uruguay, Argentina and Paraguay. Formerly abundant, nowadays it is in the Red list of endangered species for those areas. During its larval stage, it feeds on Aristolochia spp, commonly found in southern grasslands. These native grassland areas are diminishing, being converted to crops and pastures, causing habitat loss for Aristolochia and E. corethrus. This study aimed to assess the genetic diversity, population structure and demographic history of E. corethrus. We sampled eight populations from Rio Grande do Sul, Brazil and based on Cytochrome Oxidase subunit I (COI) molecular marker, our results suggest a low genetic variability between populations, presence of gene flow and, consequently, lack of population structure. A single maternally inherited-genetic marker is insufficient for population-level decisions, but barcoding is a useful tool during early stages of population investigation, bringing out genomic diversity patterns within the target species. Those populations likely faced a bottleneck followed by a rapid expansion during the last glaciation and subsequent stabilization in effective population size. Habitat loss is a threat, which might cause isolation, loss of genetic variability and, ultimately, extinction of E. corethrus if no habitat conservation policy is adopted.